EVALUASI IMPLEMENTASI SIMRS MENGGUNAKAN METODE HUMAN ORGANIZATION TECHNOLOGY (HOT)-FIT DI RAWAT INAP RS PMC - sri wahyuni; Hetty Ismainar; Rika Melyanti; Budi Hartono; Abdurrahman Hamid; Adrian Mulya (Jurnal Keperawatan Abdurrab, 2026)
In the digital era, hospitals must use integrated information systems (SIMRS) to improve service efficiency and competitiveness. This study evaluates the inpatient SIMRS at RS PMC using the HOT-Fit framework, examining human, organizational, technology, and net benefit factors. A qualitative case study was conducted in June–July 2025 with 10 informants from hospital management, IT, and clinical staff. Results show high system usage and user satisfaction: staff reported easier workflows and faster information access. Management support was strong (financing, motivation). Technically, the SIMRS has good usability, accuracy, and responsiveness, but lacks modules (e.g. nursing, finance) limiting completeness. Net benefits include faster care processes, reduced manual work, and better decision-making. To sustain and develop SIMRS, strategic plans are needed: e.g. continuous user training programs and coaching (human factor); forming a cross-disciplinary SIMRS team and scheduled evaluations (organizational); creating an IT-governance roadmap to complete missing modules and enhance cybersecurity. These measures aim to align human, organizational, and technological elements for lasting system success.